The Effect of Self-Esteem on Leadership Orientation: A Study on Students of Sports Management Department - Gunel, Ilker (Asian Journal of Education and Training, 2021)
In this study, which aims to examine the effect of self-esteem levels of students who receive sports management education on their leadership orientation, the population of this study, in which the related screening method is used among quantitative research designs, consists of students studying at the Sports Management departments of the Sports Sciences Faculties of the universities in the Central Anatolia Region. The sample of the study (female = 184, male = 131) consists of 315 students of sports management department, which was reached using the convenience sampling method, and a 95% confidence interval has been used with an error margin of 5%. Data from the participants were collected with Self-Esteem Scale and Leadership Orientation Scale. Since the data has normal distribution, parametric tests have been used: correlation to measure the relationship between two variables, and regression analysis to measure the effect of the independent variable on the dependent variable. A significant positive relationship was found with the self-esteem levels of the students and their leadership orientation in general and in sub-dimensions of task-oriented and relationship-oriented. In addition, self-esteem levels were found to have a significant effect on students’ leadership orientation in general and in task-oriented and relationship-oriented sub-dimensions. As a result, it was found that students’ self-esteem levels and leadership orientation levels are high, and as their self-esteem levels increase, their leadership orientation in general and in task-oriented and relationship-orientation sub-dimensions also increase.